Headache OSCE Part 2: A 22-Year-Old Woman Presents to the Emergency Department With the Subacute Onset of Severe Headache - Diana Barratt; Vivian Obeso; Andrew Brown (Association of American Medical Colleges, 2013)
Abstract Introduction This resource contains an objective structured clinical exam (OSCE) regarding a 22-year-old woman presenting to the emergency department with the subacute onset of headache. It is the second in a series of OSCEs assessing headaches in an emergency setting. Methods This 15-minute OSCE is part two in a series. It requires that the examinee take a detailed headache history from a standardized patient, generate an initial differential diagnosis, request and interpret diagnostic tests, and defend the final diagnosis. Five minutes for immediate and structured feedback is recommended. Criteria for passing and a grading system and have been established. Remediation plans are prescribed, depending on the type of error made by the examinee. Results This case is used at the Florida International University Herbert Wertheim College of Medicine during the third-year neurology clerkship for summative purposes. Feedback is given immediately after the encounter by the faculty. Thirty-four medical students completed this assessment. Eighty-five percent of students passed. The scores have ranged from 75-98%, with a mean of 89%. Based on survey of six medical students, 100% percent of students believed that this OSCE was an effective means to practice evaluating a patient with a headache. In addition, 100% felt that the standardized patient came across as realistic and believable. Eighty-three percent felt that the medical information given in the instructions for the scenario was sufficient to handle the interaction. Eighty percent (one student declined to answer) felt more confident and comfortable evaluating a patient with headache after this OSCE, and 83% felt the OSCE was a fair way to assess a student's ability to evaluate a patient with headache. Discussion Although the tool has not yet been administered to residents, we feel that it would be appropriate for use at the resident level. The objectives of this OSCE are aligned with the following curriculum guidelines: the neurology clerkship core curriculum guidelines, endorsed by the American Academy of Neurology (AAN); the core curriculum for first-year neurology residents, endorsed by the AAN's Headache and Facial Pain Section; and the recommended curriculum guidelines for family medicine residents, endorsed by the American Academy of Family Physicians (AAFP).